Impact of Collagen Cross-linking on Psychological Distress and Vision and Health-Related Quality of Life in Patients With Keratoconus - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
Objective: To evaluate the changes in psychological distress level and quality of life (QoL) scores of keratoconus (KC) patients 1 year after corneal collagen cross-linking (CXL). Methods: Observational cross-sectional study. Thirty-three, consecutive progressive KC patients who received CXL treatment were enrolled in the study. All patients were evaluated before and 1 year after CXL ophthalmologically and psychologically. Main outcome measures were the visual, refractive, and topographic changes and the Beck Depression Inventory, State-Trait Anxiety Inventory (STAI), Short Form-36 (SF-36), and The National Eye Institute Visual Function Questionnaire (NEI-VFQ-25). Results: There were significant improvements in the keratometric readings at flat axis, steep axis, the mean keratometric reading, the corneal astigmatism (K-ast), and the maximum keratometric reading. State-Trait Anxiety Inventory-II scores, QoL dimensions, such as physical role difficulty, general health, mental health, ocular pain, near activities, distance activities, peripheral vision, and mental health scores, and the composite score of NEI-VFQ-25, were higher after surgery. There was a positive correlation between the changes observed in K-ast and mental health; a negative correlation between the changes in K-ast and STAI-II, and a negative correlation between the changes in mental health and STAI-II. Change in STAI-II has significantly predicted the improvement observed in general health. Conclusions: Our results suggested lower trait anxiety and better vision-related and health-related QoL in KC patients 1 year after successful CXL treatment. Better QoL in these patients seems to be related not only with the visual and refractive results but also improvement observed in trait anxiety.
Keywords: Anxiety; Collagen cross-linking; Depression; Keratoconus; Quality of life; SENSITIVITY; SEVERITY